2008
DOI: 10.1007/s11046-008-9123-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Profile of Cryptococcal Meningitis Patients in Rio Grande do Sul, Brazil

Abstract: Cryptococcosis is a major opportunistic mycosis which has meningitis as its most frequent clinical presentation and can be fatal in the absence of antifungal therapy. The aetiological agents are Cryptococcus neoformans, which affects mainly immunocompromised subjects, and C. gattii, the aetiologic agent for cryptococcosis in healthy individuals. A recent outbreak of cryptococcosis on Vancouver Island, Canada, raised the level of concern about the epidemiology of this disease. In Brazil, between 1980 and 2002, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 26 publications
6
25
0
5
Order By: Relevance
“…Overall, cryptococcosis, as well as the endemic mycoses (blastomycosis, coccidioidomycosis, histoplasmosis, and paracoccidioidomycosis), occurs more often among adult males; however, the prevalence of latent infections is comparable in both sexes (14,33,51). Surveys of delayed-type hypersensitivity and other immunological evidence have demonstrated that for endemic mycoses, the gender disparity is not due to sex-related differences in exposure or infection rates (51).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, cryptococcosis, as well as the endemic mycoses (blastomycosis, coccidioidomycosis, histoplasmosis, and paracoccidioidomycosis), occurs more often among adult males; however, the prevalence of latent infections is comparable in both sexes (14,33,51). Surveys of delayed-type hypersensitivity and other immunological evidence have demonstrated that for endemic mycoses, the gender disparity is not due to sex-related differences in exposure or infection rates (51).…”
Section: Discussionmentioning
confidence: 99%
“…grubii, la variedad neoformans ha sido más frecuente en ciertas ubicaciones geográficas, como India, Francia, Italia y Dinamarca y está asociada con infecciones en las personas más viejas como ancianos, la presencia de lesiones en la piel y el uso de corticosteroides 14 . El serotipo A parece ocurrir más en pacientes con VIH y en edades comprendidas entre 20 y 40 años 15 , lo que corrobora con nuestro estudio donde los pacientes tenían 24 años y 39 años.…”
Section: Discussionunclassified
“…Cryptococcosis, caused by Cryptococcus neoformans, is an important infectious disease with a worldwide presence (1,9,10). Cryptococci are encapsulated saprophytic yeasts often found in soil contaminated with avian excreta (11).…”
Section: Discussionmentioning
confidence: 99%